Iterations of mean-type mappings and invariant means - Matkowski, Janusz (Annales Mathematicae Silesianae, 1999)
It is shown that, under some general conditions, the sequence of iterates of every mean-type mapping on a finite dimensional cube converges to a unique invariant mean-type mapping. Some properties of the invariant means and their applications are presented.